A Photoactive Carbon‐Monoxide‐Releasing Protein Cage for Dose‐Regulated Delivery in Living Cells. (2nd September 2015) - Fujita, Kenta; Tanaka, Yuya; Abe, Satoshi; Ueno, Takafumi
Abstract: Protein cages can serve as bioinorganic molecular templates for functionalizing metal compounds to regulate cellular signaling. We succeeded in developing a photoactive CO‐releasing system by constructing a composite of ferritin (Fr) containing manganese–carbonyl complexes. When Arg52 adjacent to Cys48 of Fr is replaced with Cys, the Fr mutant stabilizes the retention of 48 Mn–carbonyl moieties, which can release the CO ligands under light irradiation, although wild‐type Fr retains very few Mn moieties. The amount of released CO is regulated by the extent of irradiation. This could reveal an optimized dose for cooperatively activating the nuclear factor κB (NF‐κB) in mammalian cells and the tumor necrosis factor α (TNF‐α). These results suggest that construction of a CO‐releasing protein cage will advance of research in CO biology.